A bridge weigh-in-motion algorithm for fast-passing railway freight vehicles considering bridge-vehicle interaction. (1st December 2022) - Xiao, Xiang; Pi, Dongping; Zhu, Qing
Abstract: Accurate weight information of freight vehicles is of great value for the assessment and maintenance of railway infrastructures. Existing bridge weigh-in-motion (BWIM) methods can introduce errors when the vehicle speed is high so that the dynamic effect cannot be filtered by signal processing. This paper proposes a novel BWIM algorithm for fast-passing railway freight vehicles, in which the dynamic coupling of the VB system is utilized. An extended state-space model with unknown mass parameters for the time-dependent VB system is established. Based on the model, an SPKF algorithm with a high convergence rate for identifying the mass parameters is proposed. Numerical examples of freight vehicles passing a 40 m railway bridge with a speed up to 120 km/h are presented to validate the effectiveness of the proposed algorithm.